2016
DOI: 10.4238/gmr.15048728
|View full text |Cite
|
Sign up to set email alerts
|

Molecular thrombophilic profile in Mexican patients with idiopathic recurrent pregnancy loss

Abstract: Idiopathic recurrent pregnancy loss (IRPL) is defined by three or more consecutive miscarriages occurring before the twentieth week of gestation as a result of unidentified etiological factors. The results of previous studies have indicated that prothrombotic factors play a pathogenic role in early and late pregnancy. This study aimed to identify inherited prothrombotic and hypofibrinolytic risk factors in Mexican-Mestizo patients with IRPL. Fifty-six women with IRPL and 50 control women with at least two full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 29 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…Finally, a total of 26 case-control studies with 3,140 RPL cases and 3,370 controls were included in the present meta-analysis. 14 15 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 The characteristics of the selected studies are summarized in Table 1 . Of these, 10 case-control studies involving 1,391 cases and 1,292 controls were conducted in Caucasians, 25 26 28 31 36 37 40 41 44 48 10 case-control studies in the west-Asians, 15 27 29 32 33 39 42 45 47 with 984 cases and 1,108 cases, 4 case-control studies in the East-Asians, 14 30 34 with 670 cases and 880 controls, 1 study involving 55 cases and 50 controls in Latinos, 43 and 1 study with 40 cases and 40 controls in Africans.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, a total of 26 case-control studies with 3,140 RPL cases and 3,370 controls were included in the present meta-analysis. 14 15 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 The characteristics of the selected studies are summarized in Table 1 . Of these, 10 case-control studies involving 1,391 cases and 1,292 controls were conducted in Caucasians, 25 26 28 31 36 37 40 41 44 48 10 case-control studies in the west-Asians, 15 27 29 32 33 39 42 45 47 with 984 cases and 1,108 cases, 4 case-control studies in the East-Asians, 14 30 34 with 670 cases and 880 controls, 1 study involving 55 cases and 50 controls in Latinos, 43 and 1 study with 40 cases and 40 controls in Africans.…”
Section: Resultsmentioning
confidence: 99%
“…D allele frequency in our Egyptian sample was close to that reported among women withRPL in different studies from different ethnic groups. [ 8 9 22 29 31 32 33 34 ] In contrary, other studies did not find an association between ACE I/D gene polymorphism and RPL. [ 23 24 25 26 27 28 30 ] Table 5 shows the allele frequency of ACE I/D gene polymorphism of our studied sample in comparison with other studies from different countries.…”
Section: Discussionmentioning
confidence: 97%
“…In the literature, no studies detail differences in the severity of cardiovascular events based on various polymorphisms. A study has demonstrated that patients with C677T homozygous mutations have an increased risk of venous thromboembolism (VTE) and thromboembolism (23%) compared to compound heterozygous C677T-A1298C (16%) [5]. Furthermore, Day et al demonstrated that variants in MTHFR may influence the progression or severity of pulmonary vascular disease [3].…”
Section: Discussionmentioning
confidence: 99%